Keterlibatan Orang dengan Gangguan Jiwa dalam Proses Pemilu: Tinjauan Hukum Perdata terhadap Kewenangan dan Batasan - Muslimah, Arsas (UM Purwokerto Press, 2024)
The involvement of people with mental illness in elections is an important issue in the context of civil law, human rights and political participation. In Indonesia, although the 1945 Constitution and related laws provide equal rights for all citizens, including people with mental disabilities, there is still debate about their eligibility to participate in elections. Several articles in the Civil Code state that people with mental illness are not legally competent, while electoral laws allow their participation if they are not permanently mentally impaired. This research examines the legal basis and limitations of the authority of persons with mental disabilities in elections, and analyzes the existing legal uncertainties. It is hoped that the results of this research can provide recommendations to improve political inclusion for people with mental disabilities in Indonesia.